2021
DOI: 10.3390/ma14247733
|View full text |Cite
|
Sign up to set email alerts
|

Post-Fatigue Fracture and Marginal Behavior of Endodontically Treated Teeth: Partial Crown vs. Full Crown vs. Endocrown vs. Fiber-Reinforced Resin Composite

Abstract: Objectives: To investigate in vitro post-fatigue fracture behavior of endodontically treated molars having been differently restored. Methods: A total of 120 extracted human molars were used. A total of 120 specimens in 14 test groups and one control group (n = 8) were root canal treated. After postendodontic sealing and build-up (AdheSE Universal, SDR), additional MOD preparations were cut. Postendodontic restorations were: Direct restorations (Tetric EvoCeram BulkFill bonded with AdheSE Universal and EverX P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
20
0
3
Order By: Relevance
“…RD regarding the fracture of restorations proved it. In fact, we found out two in vitro studies comparing the difference of fracture resistance between onlays/partial crowns and full crowns [ 56 , 57 ]. Yu et al [ 56 ] investigated the fracture resistance and fracture modes of IPS e.max onlays and crowns, finding that ceramic onlays and crowns had the similar fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RD regarding the fracture of restorations proved it. In fact, we found out two in vitro studies comparing the difference of fracture resistance between onlays/partial crowns and full crowns [ 56 , 57 ]. Yu et al [ 56 ] investigated the fracture resistance and fracture modes of IPS e.max onlays and crowns, finding that ceramic onlays and crowns had the similar fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mode II (less than half of the crown is lost) was the main fracture type of onlays restoring the endodontically treated teeth while severe fractures (Type V, a severe fracture of the crown and/or tooth) occurred mainly in the endodontically treated teeth restored by crowns [ 56 ]. Frankenberger et al [ 57 ] reported that no significant difference was found between the partial crowns and full crowns in the e.max group regarding post-fatigue fracture resistance. These laboratory outcomes were in agreement with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the recurrent infection-related aspects are not the unique cause of long-term failure, since the mechanical fracture of endodontically treated teeth can occur [ 5 , 6 ]. As thoroughly demonstrated, the post-endodontic restoration of teeth with crowns or cast restorations does not influence treatment success based on periapical healing as long as there is no sign of coronal leakage; however, it can influence the survival rate of teeth over time, reducing the mechanical failure rate [ 7 , 8 ]. Despite this, the literature findings are still unclear regarding the relationship between the long-term outcome of RCT and the post-endodontic treatment plan with regard to the material of choice [ 9 , 10 ].…”
mentioning
confidence: 99%
“…Firstly, the restoration should not interfere with the mechanical load of the tooth, protecting it from fractures arising from occlusal loads [ 6 ]. Secondly, the material should guarantee an intrinsic integrity and a good marginal adaptation over time in order to avoid leakage that could cause bacteria infiltration and the secondary contamination of the root canal system [ 7 ]. However, the most recent available data on the survival and failure rates of endodontically treated teeth according to the material used for the post-endodontic restoration in relation to the prosthodontic plan are still ambiguous, and clinicians often develop the treatment plan based on their personal judgment rather than on scientific evidence [ 12 ].…”
mentioning
confidence: 99%